Risk factors for weaning failure of mechanical ventilation in adults - Castillo-Saavedra, Tom (2023)
Background: Weaning of the mechanical ventilation (MV) is a complex process and when it fails, it can increase the risks of complications and expenses in health systems. Objective: To identify risk factors for failed weaning in adults with MV. Materials and Methods: Case-control study carried out in patients older than 18 years admitted to the intensive care unit of a tertiary care hospital. Cases were identified as failed weaning (FW) of MV, and controls were simple weaning. Patients from another hospital with MV were excluded. Risk factors studied were high nutritional risk by the modified Nutric score, late enteral nutrition, positive water balance (WB) and the absence of physical therapy prior to weaning. OR was calculated with a significance < 0.05 for bivariate, multivariate, and adjusted analysis. Results: 105 patients were included, 35 cases and 70 controls. The bivariate analysis found that high nutritional risk (OR = 2.5; 95% CI = 1.1 - 5.9; p = 0.027) was a risk factor, but the multivariate analysis did not confirm it. Late enteral nutrition (OR = 1.2; 95% CI = 0.4 – 3.4), positive WB (OR = 0.7; 95% CI = 0.3 – 1.7) and the absence of respiratory physiotherapy (OR = 0.2; 95% CI = 0.004 – 0.011) were not risk factors for FW. Conclusions: High nutritional risk, late enteral nutrition, positive BH and the absence of respiratory physiotherapy before weaning were not risk factors for FW.